A study of factors affecting the entrepreneurial interest of Widya Husada Semarang University Students - Manurung, Mona Tiorina; Prameswari, Fanniya Dyah (Trigin Publisher, 2025)
Entrepreneurship plays a strategic role in shaping the economic development of a country, especially through its contribution in creating job opportunities and absorbing the workforce. However, only a small number of university graduates show interest and courage to start their own business and manage it independently. This study aims to analyze the influence of entrepreneurship education received by students, most of whom come from a health-related academic background during their studies at Widya Husada Semarang University (UWHS) along with entrepreneurial motivation, family environment, and income expectations on their interest in becoming entrepreneurs after graduation. This research uses a descriptive quantitative approach with an explanatory research design. The study included 90 undergraduate participants from UWHS, spanning the 2019 to 2021 academic years, all of whom had finished the entrepreneurship curriculum. Statistical evaluation was performed through SPSS, employing multiple linear regression analysis alongside hypothesis assessment. The results indicate that exposure to entrepreneurial training, intrinsic drive, and anticipated financial gains significantly and favorably influence students' inclination toward entrepreneurship. Conversely, familial surroundings demonstrate an adverse yet statistically negligible impact. Collectively, these predictors account for 76.9% of fluctuations in entrepreneurial aspirations, with external variables beyond the study’s scope contributing to the residual 23.1%. These results can serve as a basis for developing campus policies related to the integration of entrepreneurship curriculum that is responsive to the background of health science students. This study also contributes to the literature on the development of entrepreneurial interest in health-focused higher education institutions in Indonesia.